Large energy storage density in BiFeO3-BaTiO3-AgNbO3 lead-free relaxor ceramics. Issue 8 (July 2020) - Sun, Haonan; Wang, Xiangjian; Sun, Qinzao; Zhang, Xiaoxiao; Ma, Zhuang; Guo, Mengyao; Sun, Buwei; Zhu, Xiaopei; Liu, Qida; Lou, Xiaojie
Abstract: Lead-free (0.70- x )BiFeO3 -0.30BaTiO3 - x AgNbO3 +5‰mol CuO (abbreviated as BF-BT- x AN) ceramics were fabricated using a modified thermal quenching technique. BF-BT- x AN ceramics are of a perovskite structure with morphotropic phase boundary (MPB) and show strong relaxor properties. Remarkably, the high recoverable energy storage density of 2.11 J/cm 3 is obtained for BF-BT- x AN with x  = 0.14. For the x = 0.14 ceramics, its energy storage efficiency is as high as 84 % at relative low field of 195 kV/cm, together with an outstanding thermal stability in a broad temperature range from 25 °C to 150 °C. In addition, this ceramic maintains superior energy storage performance even after 8 × 10 4 electrical cycles due to its high densification after doping Ag2 O and Nb2 O5 . The result suggests that lead-free BF-BT- x AN ceramics may be promising candidate for dielectric energy storage application.